2024
DOI: 10.1002/adma.202311411
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Built‐In Electric Field in a Self‐Assembled Zeolitic Imidazolate Framework/MXene Nanocomposites for Microwave Absorption

Zhenguo Gao,
Aamir Iqbal,
Tufail Hassan
et al.

Abstract: The use of heterointerface engineering, which can play a pivotal role in producing advanced microwave‐absorbing materials, to prepare a zeolitic imidazolate framework (ZIF)–MXene nanocomposite is reported herein. The ZIF–MXene composites can be prepared by electrostatic self‐assembly of negatively charged titanium carbide MXene flakes and positively charged Co‐containing ZIF nanomaterials. This approach effectively creates abundant Mott–Schottky heterointerfaces exhibiting a robust built‐in electric field (BIE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…From Figs. 4 e and S25, it can be found that Mo–MXene/Mo–Sn sulfides exhibit excellent polarization loss [ 58 , 59 ]. Moreover, the presence of MoS 2 can provide additional conduction loss for the Mo–MXene/Mo–Sn sulfide heterostructures and enhance the attenuation ability [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Figs. 4 e and S25, it can be found that Mo–MXene/Mo–Sn sulfides exhibit excellent polarization loss [ 58 , 59 ]. Moreover, the presence of MoS 2 can provide additional conduction loss for the Mo–MXene/Mo–Sn sulfide heterostructures and enhance the attenuation ability [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…When semiconductor junctions and Mott–Schottky junctions are built in Mo–MXene, MoS 2 , and Sn 2 S 3 , the electron density of the total density of orbital states (TDOS) of Mo–MXene/Mo–Sn sulfides changes (Fig. S45) [ 59 ]. This indicates that the construction of BIEF helps to modulate the electron migration ability of Mo–MXene/Mo–Sn sulfides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the larger the radius of the semicircle, the more pronounced the indication of polarization becomes. This could be attributed to the capacitance-like behavior exhibited by heterogeneous interfaces when subjected to electromagnetic waves, leading to charge redistribution at said interface. Notably, the straight line at the end of the Cole–Cole curve progressively became longer with an increase in the MXene content. This implied that the conduction loss of the materials enhanced, which was attributed to the presence of heterogeneous interfaces, modified the rate or the mode of electron transfer, thus modulating the conduction loss.…”
Section: Resultsmentioning
confidence: 99%
“…This contributes to the optimization of the impedance-matching characteristics of the composite aerogel. To elucidate the magnetic storage and dissipation capabilities of composite aerogels, we further analyzed their complex permeability ( μ′ and μ″ ). , Figure S8a,b shows that the μ′ and μ″ values of Fe 3 O 4 /MoS 2 composite range from 0.95 to 1.05 and from 0 to 0.05, respectively, and fluctuate to varying degrees across the tested frequency range, implying a strong responsiveness to EM wave and notable magnetic storage/loss capacities. As illustrated in Figure d,e, the μ′ and μ″ values of GM and FMGM-1 are close to constants 1 and 0, respectively, indicating their weak magnetic nature, attributed to the low content of magnetic component.…”
Section: Resultsmentioning
confidence: 99%